The Description of Lipid Profile on Injectable DMPA Contraception Acceptors in Public Health Center Banjarsengon, Jember District - Ririn Handayani; Rizki Fitrianingtyas (Journal of Ners and Midwifery, 2021)
Injectable DMPA contraception can cause changes in lipoprotein metabolism. Changes in fat metabolism occur because of the hormonal influence of progesterone, causing disruption of the balance of lipid profiles in the body. The change in serum lipid profile (trgliseride, total cholesterol, HDL and LDL) in long-term use of DMPA is a risk factor for atherosclerosis and cardiovascular disease. The purpose of this study was to look at the description of the lipid profile at 3 months injection acceptors. The design of the study was descriptive. The population in this study was 76, the number of samples that met the inclusion and exclusion criteria in this study was 30. Examination of the lipid profile was carried out with an enzymatic colorimetric (cholesterol oxidase method / CHOD PAP). The results of lipid profile examination showed that 13.33% had high cholesterol levels, 3.33% had high triglyceride levels, 13.33% had high HDL levels, 20% had high LDL levels and 3.33% have very high LDL levels. The conclusion of this study was long term use of DMPA injection contraception could cause changes in the lipid profile, so it is recommended for acceptors who want to use contraception in the long term to use MKJP as an option so as not to affect the fat profile in the body.